Neuroprotective impacts of chrysin against clonazepam induced cognitive deficits in male rats - Hend A. Sabry, Mai M. Zahra, Shimaa A. Haredy, Amany S. Amer (Journal of Applied Pharmaceutical Science, 2023)
The therapeutic effects of Clonazepam (CZP), a classic anti-anxiety drug, are accompanied by several neurodegenerations and neural disorders in patients. Also, Chrysin is a flavonoid that naturally exists in many plants and honey; it has various pharmacological effects, including anti-cancer, antioxidant, and anti-inflammations, and it has a neuroprotective effect. The purpose of this work is to evaluate the influences of chronic treatments with Chrysin on behavior and neurochemical fluctuations induced by CZP treatment. Forty male rats were classified into four groups with one of them acting as the control group receiving 1% Tween 80; the CZP group was treated with 2 mg kg−1day−1; the Chrysin group was treated with 50 mg kg−1day−1; the CZP + Chrysin group was treated with the same above-mentioned doses of CZP and Chrysin. All animals were orally treated every day for 6 weeks. Open field and Y maze tasks were performed before decapitation. Then, gamma-aminobutyric acid (GABA), glutamic acid, monoamines (norepinephrine, dopamine, and serotonin) and their metabolites (homovanillic acid, 3,4-dihydroxyphenylacetic acid, and hydroxy indoleacetic acid, respectively), and DNA fragmentation [8-hydroxy-2–deoxyguanosine (8-HdG)] were evaluated in the brain cerebral cortex, hippocampus, and striatum, while brain-derived neurotrophic factor (BDNF) and calcium ATPase (Ca-ATPase) were measured in the whole brain. The results showed that Chrysin treatment improves GABA, glutamic acid, monoamines, and their metabolites in the three brain areas, whereas it inhibits DNA fragmentation 8-HdG and BDNF and modifies downregulation of Ca-ATPase persuaded by CZP treatment at p < 0.05. Moreover, Chrysin treatment intensely reverses the consequent behavioral alternations which were elevated by Y maze and open field tests changed by CZP treatment. Overall, results recommended that Chrysin exerts anxiolytic-like effects similar to benzodiazepines and it can produce neuroprotective effects against CZP treatment.